High prevalence of HIV and non‐communicable disease (NCD) risk factors in rural KwaZulu‐Natal, South Africa - van Heerden, Alastair (J Int AIDS Soc, 2017)
INTRODUCTION: South Africa faces epidemics of HIV and non‐communicable diseases (NCDs). The aim of this study was to characterize the prevalence of non‐communicable disease risk factors and depression, stratified by HIV status, in a community with a high burden of HIV. METHODS: We conducted a home‐based HIV counselling and testing study in KwaZulu‐Natal, South Africa between November 2011 and June 2012. Contiguous households were approached and all adults ≥18 years old were offered an HIV test. During follow‐up visits in January 2015, screening for HIV, depression, obesity, blood glucose, cholesterol and blood pressure were conducted using point‐of‐care tests. RESULTS: Of the 570 participants located and screened; 69% were female and 33% were HIV‐positive. NCD risk factor prevalence was high in this sample; 71% were overweight (body mass index (BMI) 25 to 29.9 kg/m(2)) or obese (BMI≥30 kg/m(2)), 4% had hyperglycaemia (plasma glucose >11.0 mmol/l/200 mg/dl), 33% had hypertension (HTN, >140/90 mmHg), 20% had hyperlipidaemia (low density cholesterol >5.2 mmol/l/193.6 mg/dl) and 12% had major depressive symptoms (nine item Patient Health Questionnaire ≥10). Of the 570 participants, 87% had one or more of HIV, hyperglycaemia, HTN, hyperlipidaemia and/or depression. Over half (56%) had two or more. Older age and female gender were significantly associated with the prevalence of both HIV infection and NCD risk factors. Around 80% of both HIV‐positive and negative persons had one of the measured risk factors (i.e. obesity, hyperglycaemia, hyperlipidaemia, HTN), or depression. CONCLUSIONS: In a community‐based sample of adults in KwaZulu‐Natal, South Africa, the prevalence of both HIV infection and NCD risk factors were high. This study is among the first to quantify the substantial burden of NCD risk factors and depression in this non‐clinic based population.